2015
DOI: 10.1158/1055-9965.epi-15-0289
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Biomarker Discovery and High-Throughput DNA Sequencing Are Possible Using Long-term Archived Serum Samples

Abstract: Background: The impacts of long-term storage and varying preanalytical factors on the quality and quantity of DNA and miRNA from archived serum have not been fully assessed. Preanalytical and analytical variations and degradation may introduce bias in representation of DNA and miRNA and may result in loss or corruption of quantitative data.Methods: We have evaluated DNA and miRNA quantity, quality, and variability in samples stored up to 40 years using one of the oldest prospective serum collections in the wor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 43 publications
2
43
0
2
Order By: Relevance
“…While the long-time storage did not reduce miRNA yields the preanalytical conditions like different clotting times had a significant effect on miRNA abundances. 27 Further evidence for the stability of miRNAs in stored samples came from a real-time PCR analysis that was performed on a panel of 8 miRNAs from samples that were stored for 12 months at ¡80 C. 28 Independent of the influence of the duration of the storage it is important to address the difference between various collection protocols. Although the majority of the protocols is on collections of sera, there is a multitude of variations including scenarios that required the collection of plasma or of whole blood, which is later used for serum or plasma isolation, scenarios that largely vary in terms of storage duration and storage temperature of either blood, serum or plasma, and protocols that vary in terms of the methods used for RNA isolation.…”
Section: Discussionmentioning
confidence: 99%
“…While the long-time storage did not reduce miRNA yields the preanalytical conditions like different clotting times had a significant effect on miRNA abundances. 27 Further evidence for the stability of miRNAs in stored samples came from a real-time PCR analysis that was performed on a panel of 8 miRNAs from samples that were stored for 12 months at ¡80 C. 28 Independent of the influence of the duration of the storage it is important to address the difference between various collection protocols. Although the majority of the protocols is on collections of sera, there is a multitude of variations including scenarios that required the collection of plasma or of whole blood, which is later used for serum or plasma isolation, scenarios that largely vary in terms of storage duration and storage temperature of either blood, serum or plasma, and protocols that vary in terms of the methods used for RNA isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions all unstable RNAs have been degraded. We have shown that the total amount of miRNA was affected by the processing of the serum and to a lesser extent by storage time 21 . Also, the number of other sncRNAs decrease with storage 47 .…”
Section: Discussionmentioning
confidence: 91%
“…f The total DNA input in samples that failed and passed 94% PCT-QCCR. g, h, i The relationship between total DNA input and call rates for Axiom, standard Illumina and Illumina FFPE protocols, respectively sequencing [9], genotyping using real-time PCR [3] and SNP array (Affymetrix) analyses [10] of Janus Serum Bank samples have been successful. However, another study concluded that genotyping with DNA extracted from serum did not provide reliable data using highthroughput multiplex approaches, but was successful using Taqman [11].…”
Section: Discussionmentioning
confidence: 99%